"Calm Down, You’ll Make it Worse": Nussbaum’s Transition-Anger as Affective Injustice - Roux, Josie (The Stellenbosch Socratic Journal, 2021)
Martha Nussbaum’s account of anger follows on neatly from the work of her liberal Western forebears. In her view, anger has neither intrinsic nor instrumental value. Anger is both normatively problematic, and counter-productive, in that it succeeds only in exacerbating injustices rather than solving them. One exception to this negative account is what she calls “Transition-Anger”, a species of anger more akin to compassionate hope that aims for positive change and amelioration. Individuals, says Nussbaum, should try to move to Transition-Anger as quickly as possible when they feel angry. Amia Srinivasan presents a striking counterargument to the traditional Western view of anger. She points out that the counterproductivity criticism gives rise to a type of affective injustice in that requiring an individual to not get aptly angry in the face of injustice out of fear of the consequences is a double injustice. In this paper, I criticise Nussbaum’s Transition-Anger by showing that it is a paradigmatic case of the affective injustice to which Srinivasan refers.